Increased Apoptosis in Subcortical Regions of The Visual Pathway in Offspring Born to Diabetic Rats - Nasim Alipour; Somaye Fallahnezhad; Javad Bagheri; Hamideh Babaloo; Fatemeh Tahmasebi; Ghasem Sazegar; Hossein Haghir (Cell Journal, 2023)
Objective: Diabetes in pregnancy is a prevalent disease that can affect the central nervous system of the fetus byhyperglycemia. This study aimed to investigate the impact of maternal diabetes on neuronal apoptosis in the superiorcolliculus (SC) and the lateral geniculate nucleus (LGN) in male neonates born to diabetic mothers.Materials and Methods: In this experimental study, female adult rats were separated into three groups: control,diabetic (induced using an intraperitoneal injection of streptozotocin), and insulin-treated diabetic [diabetes controlledby subcutaneous neutral protamine hagedorn (NPH)-insulin injection]. Male neonates from each group were euthanizedon 0, 7, and 14 postnatal days (P0, P7, and P14, respectively), and apoptotic cells were identified using TUNEL staining.Results: The numerical density per unit area (NA) of apoptotic cells was significantly higher in SC and the dorsalLGN (dLGN) in neonates born to the diabetic rats compared to the control group at P0, P7, and P14. However, insulintreatment normalized the number of apoptotic cells.Conclusion: This study demonstrated that maternal diabetes increased apoptosis in dLGN and SC of male neonatesat P0, P7, and P14.